2000
DOI: 10.1046/j.1464-410x.2000.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Q‐flap reconstruction of panurethral strictures

Abstract: Objective To review our experience with an extended Qshaped penile skin¯ap for the reconstruction of panurethral strictures. Patients and methods Between 1991 and 1999, 15 men with extensive strictures underwent a single-stage urethral reconstruction with a distal circumferential penile skin¯ap incorporating a ventral midline extension (Q-¯ap). None had undergone previous urethroplasty nor had any been circumcised. Results The Q-¯ap provided a pedicled strip of penile skin with a mean (range) length of 17 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
(18 reference statements)
0
26
0
1
Order By: Relevance
“…11 Another approach uses a fasciocuta- neous skin flap and has several avatars with incision modifications or simultaneous use of a buccal mucosa graft. [12][13][14][15][16][17] Repair with tunica albuginea was also suggested. 18 Dubey et al compared their experience with 1-stage repair using our technique and 2-stage repair for LS strictures.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another approach uses a fasciocuta- neous skin flap and has several avatars with incision modifications or simultaneous use of a buccal mucosa graft. [12][13][14][15][16][17] Repair with tunica albuginea was also suggested. 18 Dubey et al compared their experience with 1-stage repair using our technique and 2-stage repair for LS strictures.…”
Section: Discussionmentioning
confidence: 99%
“…El-Kassaby et al reported excellent results in 90% of cases upon the use of buccal mucosal grafts harvested from the lower lip in management of anterior urethral stricture [7]. Non-hirsute penile fasciocutaneous flaps constitute the most durable substitution technique for pendulous stricture disease, with long-term studies reporting 90-96% success [27]. Our experience with buccal mucosal graft urethroplasty was limited for high success we got, therefore the result to be accepted, it needs more cases.…”
Section: Discussionmentioning
confidence: 94%
“…2a-d). PSFs were developed using the detailed techniques described previously [4,8]. After splitting the flap ventrally, the pedicle was mobilized proximally to an extent that allows ventral transposition of the flap without tension.…”
Section: Methodsmentioning
confidence: 99%
“…McAninch [3] reported using the circular fasciocutaneous penile flap to treat AUS, and they summed up the experience of 66 cases in 1998 and obtained satisfactory outcome. Morey et al [4] reported an extended Q-shaped PSF for the reconstruction of panurethral strictures. Most authors have reported similar success rates of 83-93% for both the free grafts and pedicled skin flaps, but generally poorer results with the formation of a tube [5,6].…”
Section: Introductionmentioning
confidence: 99%